Life cycle, techno-economic and dynamic simulation assessment of bioelectrochemical systems: A case of formic acid synthesis. (May 2018) - Shemfe, Mobolaji; Gadkari, Siddharth; Yu, Eileen; Rasul, Shahid; Scott, Keith; Head, Ian M.; Gu, Sai; Sadhukhan, Jhuma
Graphical abstract: Highlights: Integrated dynamic simulation, LCA and techno-economic assessment framework of BES. Simultaneous wastewater treatment in anode and HCOOH synthesis in cathode by BES. Framework enables BES optimisation for resource productivity and bioremediation. Product HCOOH:Removed COD is 1:0.406 gives 4.3 units CO2 -eq GWP saving, by mass. Key to feasibility of BES is productivity gives higher LCA benefit than remediation. Abstract: A novel framework, integrating dynamic simulation (DS), life cycle assessment (LCA) and techno-economic assessment (TEA) of a bioelectrochemical system (BES), has been developed to study for the first time wastewater treatment by removal of chemical oxygen demand (COD) by oxidation in anode and thereby harvesting electron and proton for carbon dioxide reduction reaction or reuse to produce products in cathode. Increases in initial COD and applied potential increase COD removal and production (in this case formic acid) rates. DS correlations are used in LCA and TEA for holistic performance analyses. The cost of production of HCOOH is €0.015–0.005 g −1 for its production rate of 0.094–0.26 kg yr −1 and a COD removal rate of 0.038–0.106 kg yr −1 . The life cycle (LC) benefits by avoiding fossil-based formic acid production (93%) and electricity for wastewater treatment (12%) outweigh LC costs of operation and assemblage of BES (−5%), giving a net 61MJkg −1 HCOOH saving.